THE ROLE OF FOREIGN DIRECT INVESTMENT IN THE ESTABLISHMENT AND DEVELOPMENT OF ECONOMIC ENTERPRISES: AN EMPIRICAL STUDY OF LAFARGEHOLCIM COMPANY IN M’SILA - Herouz Khelifa; Mohamed Laid Khatim (International Journal of Innovative Technologies in Social Science, 2024)
This study investigates the role of foreign direct investment (FDI) in supporting and developing economic enterprises of varying sizes (micro, small, and medium-sized enterprises) during the period from 2003 to 2023. A comprehensive set of research tools was employed, including observations and interviews conducted with executives at LafargeHolcim Company in M’sila, to identify the company’s contribution and its relationship with the surrounding economic enterprises. Additionally, the study analyzed data obtained from the Ministry of Industry and Mines and the company under investigation throughout the study period. The findings reveal that FDI has a positive impact on economic enterprises. It significantly contributes to the establishment of micro and small enterprises and plays a key role in the development of small and medium-sized enterprises. These results underscore the crucial role of FDI in the establishment and development of economic enterprises.